Knowledge, attitude and perception on climate change and dietary choices in a predominantly Chinese university students population in Klang Valley - Lee, Ling Jun; En, Serene Hui Tung; Gan, Wan Ying; Satvinder, Kaur (Malaysian Society of Applied Biology, 2022)
Climate change is a public health threat that is aggravated by the food supply chain. A dietary shift to climate-friendly foods is a feasible strategy to mitigate it. This study aimed to investigate the associations between knowledge, attitude, perception towards climate change, and barriers to climate-friendly foods with dietary choices of university students in Klang Valley. A cross-sectional study was conducted among 303 Malaysian university students (71.9% Chinese) aged 18 to 30 years in Klang Valley, by using Google form to assess knowledge, attitude, perception towards climate change, barriers to climate-friendly food, and climate-friendly dietary choices. The average climate-friendly diet score (CFDS) was 0.36±2.21, with a significantly higher CFDS among females than males (p=0.012). The majority of them were having good knowledge (76.6%), a good attitude (66.3%), and a moderate level of perception (62.0%) towards climate change. About two-thirds of them reported social media as the main (63.0%) and preferred (63.7%) sources to receive information about climate change. Through multiple linear regression, barriers to climate-friendly food choices (β=-0.084; p<0.001) significantly contributed to climate-friendly dietary choices (F=4.215; p<0.001), whereby 14.9% of the variances were climate-friendly dietary choices of university students. Findings could be incorporated into dietary education to tackle barriers to climate-friendly foods among university students.